Blastocyst complementation-based rat-derived heart generation reveals cardiac anomaly barriers to interspecies chimera development - Shunsuke Yuri; Norie Arisawa; Kohei Kitamuro; Ayako Isotani (iScience)
Summary: The use of pluripotent stem cells (PSCs) to generate functional organs via blastocyst complementation is a cutting-edge strategy in regenerative medicine. However, existing models that use this method for heart generation do not meet expectations owing to the complexity of heart development. Here, we investigated a Mesp1/2 deficient mouse model, which is characterized by abnormalities in the cardiac mesodermal cells. The injection of either mouse or rat PSCs into Mesp1/2 deficient mouse blastocysts led to successful heart generation. In chimeras, the resulting hearts were predominantly composed of rat cells; however, their functionality was limited to the embryonic developmental stage on day 12.5. These results present the functional limitation of the xenogeneic heart, which poses a significant challenge to the development in mouse–rat chimeras.